Accessibility as a determinant of patterns of borrowing and researching of students in selected libraries in U.P. Diliman - De Ocampo, Jayme M.; Gonzales, Grace Marie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
Accessibility in terms of the location of the library, is an important factor to consider for the usage of books located in different libraries in U.P. Diliman. Descriptive study was done to evaluate the usage of books with multiple copies found in different unit libraries in U.P. Diliman.
Syllabus of GE subjects were gathered as a main source of data to obtain the books with multiple copies needed for this study. The researcher used the descriptive research method by determining the colleges of users found in the charge cards of books with multiple copies and tabulating them according to their colleges and from what library the books were located. Thus, describing the pattern of usage of books with multiple copies. In order to study the pattern of behavior of students of library users, the researcher distributed survey questionnaires to students from U.P. Dliman from different colleges. Stratified sampling was used to determine the sample population for the respondents.
The study shows that location of the library - its proximity - along with other factors, affect the research behavior of library users. Based on the findings of the study, the researcher highly recommends that other factors for determining the pattern of researching and borrowing of library users be identified and use other methods or research instruments to study location as a determinant. According to student's response from the survey, proximity of the library from their college is one of the strongest factor affecting their research behavior.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman -- students; Library sites -- Philippines -- Quezon City